Effects of different energy levels and ambient temperatures on serum thyroid hormones and some biochemical values in Holstein steers - Güler, T; Kul, S; Ertas, ON (Polish Soc Veterinary Sciences Editorial Office, 2006)
This W factorial study was designed to test the effects of different diet energy levels (Low: 5.39 NEf MJ/kg and High: 6.60 NEf MJ/kg) and environmental temperature (Low: 19.84 degrees C and High: 28.5 degrees C) on triiodothyronine (T-3) thyroxine (T-4) and blood serum parameters of Holstein steers. A total of 28 10-month old steers were divided into 4 groups, each containing 7 steers. According to this design, steers which were subjected to housing in barns were either offered normal energy (Barn-NE group) or high energy (Barn-HE group) diets; steers which were subjected to housing outside were also either offered normal energy (Outside-NE group) or high energy (Outside-HE group) diets. The highest levels of T-3 and T-4 were in the Outside-HE group followed by Outside-NE group, Barn-HE group and Barn-NE group, respectively (p < 0.05). Serum glucose, cholesterol and triglyceride levels were higher in all the outside groups (p < 0.05). No differences were found between the groups in the total protein, albumin, uric acid, inorganic phosphor, Ca, Na and K levels. The levels of SCOT, SGPT, amylase, alkaline phosphates and creatinin were similar in all groups. The results of the study indicated that increasing energy levels and ambient temperatures increased T-3 and T-4 levels and did not affect serum metabolites except for glucose, cholesterol and triglyceride.
Keywords: energy; ambient temperature; thyroid hormones; serum constituents